Emerging network architecture of ultrafast fixed broadband technologies and solutions - Stojce Ilcev, Dimov (International Journal of Engineering and Technology, 2020)
This article is introducing the development and emerging network architecture of the newest ultrafast fixed broadband (BB) technologies and solutions in the terrestrial telecommunication industries right across the globe. The modern ultrafast networks and access technologies are known as G.fast, Data Over Cable Service Interface Specification 3.1 (DOCSIS 3.1), and Gigabit Passive Optical Networks (GPON). The basic concepts associated with broadband communication network technologies with emphasis on the provision of multipurpose service focused on the evolution and challenging fields of the broadband communication techniques from the traditional architecture to the incorporation of virtualization services here are also discussed.Â